AUTOSOMAL DOMINANT VITREORETINOCHOROIDOPATHY: When Molecular Genetic Testing Helps Clinical Diagnosis. Issue 5 (May 2019) - Boulanger-Scemama, Elise; Sahel, Jose-Alain; Mohand-Said, Saddek; Antonio, Aline; Condroyer, Christel; Zeitz, Christina; Audo, Isabelle
Abstract : Purpose: Autosomal dominant vitreoretinochoroidopathy is an extremely rare disease, which belongs to the BEST1 -related disease spectrum. Methods: Report of five patients with an initial diagnosis of atypical rod–cone dystrophy, for whom autosomal dominant vitreoretinochoroidopathy was retrospectively diagnosed on genetic results using targeted next-generation sequencing. Each patient had a comprehensive ophthalmic examination including multimodal retinal imaging and functional evaluation. Results: Visual acuity ranged from <20/800 to 20/25. Two patients had narrowed angle with history of acute angle-closure glaucoma for one patient. Full-field electroretinogram showed severe reduction of both scotopic and photopic responses for 3/5 patients. Electrooculogram could be performed for one of the two patients with moderate alterations of full-field electroretinogram. It revealed severe light rise abnormalities with decreased Arden ratio (125% right eye, 145% left eye) in keeping with generalized severe dysfunction of the retinal pigment epithelium. On fundoscopy, the pathognomonic circumferential hyperpigmented band of the peripheral retina was totally absent in two patients. Conclusion: This report highlights the high phenotypic variability of autosomal dominant vitreoretinochoroidopathy, which may be misdiagnosed, especially in advanced forms with severe generalized photoreceptor dysfunction mimicking retinitis pigmentosa. Targeted next-generation sequencing can contribute to the proper clinical diagnosis, especially in case of atypical phenotypic features of autosomal dominant vitreoretinochoroidopathy. Abstract : Autosomal dominant vitreoretinochoroidopathy syndrome is an extremely rare disease which belongs to the BEST1-related disease spectrum. Pathognomonic clinical features are not constant with a high phenotypic variability. Here, the authors report the cases of five patients with atypical phenotype, for whom autosomal dominant vitreoretinochoroidopathy diagnosis was retrospectively assessed on the basis of genetic molecular diagnosis.